Imagery- and Verbally-Based Brooding Rumination in Adolescence: Differential Associations with Depressive Symptoms - Lawrence, Hannah R.; Siegle, Greg J.; Schwartz-Mette, Rebecca A. (Adolescent Psychiatry, 2022)
Background: Brooding rumination, or perseverative dwelling on negative cognitions, prolongs negative affect and is associated with heightened risk for depressive symptoms. Emerging research suggests that brooding rumination may be associated with more severe depressive symptoms when individuals brood in the form of mental imagery relative to verbal thoughts. Objective: The present study tested whether rumination was more highly associated with depressive symptom severity when adolescents ruminated in the form of mental imagery compared with verbal thoughts. Methods: Adolescents (N = 145) were recruited from the community surrounding a public university in the Northeastern United States. Of these adolescents, 136 were retained in analyses based on their reports of engaging in brooding rumination at least some of the time [age range: 13-17 years; M(SD)age = 15.40(1.24) years; 60.29% female, 32.35% male, 4.41% transgender, 2.94% other genders). In this crosssectional study, adolescents reported their trait levels of brooding rumination, whether they tend to ruminate in the form of mental imagery, verbal thought, or both, and completed a measure of depressive symptom severity. Moderated regression analyses were used to test whether the strength of the relation between brooding rumination and depressive symptom severity varied based on rumination style. Results: Imagery-based brooding rumination occurred in the majority of adolescents, and imagery-based rumination was more highly associated with depressive symptom severity than verbally-based rumination for female adolescents and those adolescents high in trait brooding rumination. Conclusion: Findings emphasize the potential utility of assessing and intervening on imagery-based rumination.
Keywords: gender